CLUSTER ANALYSIS IN AGRICULTURAL DECISION SUPPORT SYSTEMS DEVELOPMENT - Kurochkin, Viktor (Proceedings of National Aviation University (archive), 2016)
Purpose: With the development of unmanned aircraft technology raises the problem of creation systems of aerial data analysis to increase efficiency and reduce the cost of monitoring areas based on operational data and building automated systems of farm management combined with precision farming techniques. Methods: The review of the current state of agriculture and the development of unmanned aircraft, the use of information technologies in Ukraine compared to more developed countries made. The modern approach to imaging and conducted own research of the possibilities of image processing system based on cluster analysis. Results: Shown that the level of integration of information technology in Ukraine is quite low, in contrast to other developed countries, where there is active development of geographic information systems, including for agricultural purposes. Unmanned aerial vehicles developed in Ukraine, as evidenced by the development of the legal sphere and the presentation of definition of the category. Image processing based on cluster analysis provides data suitable for further analysis and give an idea of the structure of the area, the presence of abnormalities and the general condition of farmland. Discussion: Cluster analysis of digital images of agricultural areas is a promising area of further research that could be the basis for building complex decision support systems for the development of precision farming including in Ukraine and increase the efficiency of farming, as well as an additional tool for determining the state of the areas for evaluation and prognostication.